A competency-based coach education in the Netherlands - van Klooster, T.; Roemers, J. (International Journal of Coaching Science, 2011)
The article discusses the development, philosophy, programme, and results of TopCoach5 in the Netherlands. It says that Amsterdam University of Applied Sciences (Hva) and Hanze University Groningen partnered to establish the programme, which is considered the highest coach programme in the country. It states that the competency-based TopCoach5 defines four professional roles, including the expert, practical leader, and skills trainer. It adds that students undergo competence tests.